An algebraic q-deformed form for shape-invariant systems - Aleixo, ANF; Balantekin, A. B.; Ribeiro, MAC (Iop Publishing Ltd, 2003)
A quantum deformed theory applicable to all shape-invariant bound-state systems is introduced by defining q-deformed ladder operators. We show that these new ladder operators satisfy new q-deformed commutation relations. In this context we construct an alternative q-deformed model that preserves the shape-invariance property presented by the primary system. q-deformed generalizations of Morse, Scarf and Coulomb potentials are given as examples.